Pilot randomised controlled trial of Help4Mood, an embodied virtual agent-based system to support treatment of depression. (September 2016) - Burton, Christopher; Szentagotai Tatar, Aurora; McKinstry, Brian; Matheson, Colin; Matu, Silviu; Moldovan, Ramona; Macnab, Michele; Farrow, Elaine; David, Daniel; Pagliari, Claudia; Serrano Blanco, Antoni; Wolters, Maria; et al.
Introduction: Help4Mood is an interactive system with an embodied virtual agent (avatar) to assist in self-monitoring of patients receiving treatment for depression. Help4Mood supports self-report and biometric monitoring and includes elements of cognitive behavioural therapy. We aimed to evaluate system use and acceptability, to explore likely recruitment and retention rates in a clinical trial and to obtain an estimate of potential treatment response with a view to conducting a future randomised controlled trial (RCT). Methods: We conducted a pilot RCT of Help4Mood in three centres, in Romania, Spain and Scotland, UK. Patients with diagnosed depression (major depressive disorder) and current mild/moderate depressive symptoms were randomised to use the system for four weeks in addition to treatment as usual (TAU) or to TAU alone. Results: Twenty-seven individuals were randomised and follow-up data were obtained from 21 participants (12/13 Help4Mood, 9/14 TAU). Half of participants randomised to Help4Mood used it regularly (more than 10 times); none used it every day. Acceptability varied between users. Some valued the emotional responsiveness of the system, while others found it too repetitive. Intention to treat analysis showed a small difference in change of Beck Depression Inventory II (BDI-2) scores (Help4Mood –5.7 points, TAU –4.2). Post-hoc on-treatment analysis suggested that participants who used Help4Mood regularly experienced a median change in BDI-2 of –8 points. Conclusion: Help4Mood is acceptable to some patients receiving treatment for depression although none used it as regularly as intended. Changes in depression symptoms in individuals who used the system regularly reached potentially meaningful levels.